Горпинич В. О., Прийменко С. Ю. Катойконімія французької мови - Лучик, В. (Мовознавство, 2009)
Рецензія на книгу: Горпинич В. О., Прийменко С. Ю. Катойконімія французької мови. Д. : ДНУ, 2008,— Вип. 32, — 214 с.